2021
DOI: 10.1155/2021/9695139
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Research and Test Verification of the Seismic Response of a Multistage Series Liquid Tank

Abstract: Liquid storage tanks are lifeline structures and strategically very important. Heavy damages or even collapse of these facilities subjected to strong earthquakes may cause disastrous consequences. In this paper, the seismic response of a multistage series liquid storage tank was simulated by a finite element method and verified by a scaled-down experiment. The structural flexibility of the tank and the liquid-structure coupling characteristics between the liquid and tank wall were considered in the research. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Leng et al [12] studied the bidirectional vibration of offshore wind turbines (OWTs) due to misalignment of wind and wave loads. Yao et al [13] used the finite element method to simulate the seismic response of a multistage series fed liquid tank, considering the structural flexibility of the tank and the liquid-solid coupling characteristics between the liquid and the tank wall. Li and Wang [14] studied the seismic dynamic responses of a scaffold water tower with a sloshing water body and found that the water sloshing in the water tank prolonged the natural seismic dynamic period of the structure and reduced the displacement of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Leng et al [12] studied the bidirectional vibration of offshore wind turbines (OWTs) due to misalignment of wind and wave loads. Yao et al [13] used the finite element method to simulate the seismic response of a multistage series fed liquid tank, considering the structural flexibility of the tank and the liquid-solid coupling characteristics between the liquid and the tank wall. Li and Wang [14] studied the seismic dynamic responses of a scaffold water tower with a sloshing water body and found that the water sloshing in the water tank prolonged the natural seismic dynamic period of the structure and reduced the displacement of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical spring-mass tank model considerably simplifies computation of liquid storage tanks seismic behavior. Although this modelling approach is not sufficient to monitor change in the liquid level and liquidstructure interaction due to liquid sloshing, the approach is computationally cheap, simple to develop, and adequate for the main objective of this study [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%